STRATEGI DAKWAH MELALUI KREATIVITAS SANTRI DALAM MEWUJUDKAN ECO PESANTREN DI PONDOK PESANTREN ASY-SYARIFY PANDANWANGI KECAMATAN TEMPEH KABUPATEN LUMAJANG - Zainul Arifin (PT. Intelek Cendikiawan Nusantara, 2024)
The Eco pesantren program as a model of environmental education in pesantren has attracted the attention of scientists and researchers, and nationally the Ministry of Environment in collaboration with the Ministry of Religious Affairs launched the program on 5-6 March 2008 in Pondok Gede. The purpose of this research is to find out